Grammar in textbooks of the Secondary Level of Argentina - Cárdenas, Viviana (2023)
School grammar has been studied in Argentina from the glotopolitical perspective and linguistic historiography, but it has not been approached from a pedagogical perspective. This article asks about the different approaches to grammar teaching in Argentinean secondary school textbooks from the second third of the twentieth century to the present day. In addition, it takes into account the impact on school grammar of state policies for this level of education and the transformations in linguistic theories. In that sense, a corpus of six textbooks corresponding to the first three years of secondary education in Argentina was selected, using epistemological criteria. A contrastive analysis of the place of grammar, objectives and teaching methods was carried out. The results show that, in the books analysed, the tension between grammar as a normative discipline and grammar as a scientific discipline is resolved differently in each case on the basis of two axes: educational and linguistic policy and the theories about language that underpin school grammar.